REFOUNDING BIOMEDICAL ETHICS AT THE CROSSROADS OF CUBAN AND FRENCH EXPERIENCES - MOULIN, Anne Marie (MEDECINE LEGALE DROIT MEDICAL, 2025)
A joint French-Cuban meeting on Biomedical Ethics and New Biotechnologies was held in 2016. Anne Marie Moulin recalls the ancient foundation of medical ethics and its recent history. She points to the multiplication of texts of reference, too often originated exclusively in the Western and English-speaking world, and expresses her anxiety facing the risk of an excessive bureaucratization of bioethics and the markedly formal character of the texts, marking a gap with the actual practices in the field. On these subjects Cuba has provided reflections largely ignored because of the embargo, original because of the specific features of its health system: the close patient-family doctor relationship, the coherence of the team responsible for the individual’s care, and overall the short path existing between discovery and applications. All these orientations foster new perspectives, which should be discussed further during future meetings and exchange between French and Cuban researchers.